EARLY CLEFT LIP REPAIR: A LONG TERM FOLLOW-UP - Moenadjat, Yefta (Universitas Airlangga, 2024)
Highlights: Early cleft repair benefits patients by reconstructing near-normal lip anatomy that persists after ten to fifteen years. The early procedure did not result in muscular or maxillary hypoplasia in long-term follow-ups; rather, development occurred in tandem with normal growth. Abstract: Introduction: Published reports on the long-term outcomes of cleft lip surgery within the Indonesian population are limited, especially for those treated early in the neonatal period. This study presents follow-up data on early-managed cases, aiming to objectively evaluate the long-term results of such management. Case Illustration: A newborn with a complete unilateral cleft lip and palate had surgery on day two, achieving a symmetrical lip and nasal base. At 12 months, cleft palate surgery was performed. Fifteen years later, the patient sought a lip revision, expressing satisfaction with the results and opting against further procedures. Case 2: Another newborn with an incomplete cleft underwent surgery on day five, followed by palate repair at 12 months. Ten years later, the parents reported satisfaction with the outcomes and no desire for further revisions. Discussion: The discussion focused on the merit of early management and no negative impact on muscular and maxillary growth. Conclusion: The positive effects of early management through muscle management were observed in the long-term follow-up, as shown in these two reported cases.